Circulating MicroRNA as a Non-Invasive Prognostic Biomarker in Traumatic Brain Injury: A Narrative Review of Current Evidence and Translational Considerations for Resource-Limited Settings - Rezka Fadillah Yefri; Muhana Fawwazy Ilyas; Aji Wahyu Wardhana; Azhar Farisyabdi Kurniawan; Mustaqim Prasetya; Abrar Arham (Talenta Universitas Sumatera Utara, 2026)
Background: Traumatic brain injury (TBI) is a leading cause of neurological morbidity and mortality worldwide, with a disproportionate burden in low- and middle-income countries, including Indonesia. Prognostic assessment continues to rely on clinical scales such as the Glasgow Coma Scale (GCS) and on computed tomography, both of which have limited availability or variable performance in resource-constrained settings. Circulating microRNAs (miRNAs) are small non-coding RNAs notable for their stability in blood and quantifiability using widely available reverse transcription quantitative polymerase chain reaction (RT-qPCR) techniques, and they have emerged as candidate prognostic biomarkers after TBI. Objectives: This narrative review synthesizes current evidence on circulating miRNAs as non-invasive prognostic biomarkers in TBI and examines translational and implementation considerations within the Indonesian and broader low-resource neurosurgical context. Methods: A structured literature search was conducted in PubMed, Scopus, Google Scholar, and Cochrane for English-language human studies published between 2015 and 2024, using the keywords “microRNA”, “traumatic brain injury”, “prognosis”, and “biomarker”. After PRISMA-based screening, 32 studies were retained for narrative synthesis and complemented by foundational methodological references and high-quality reviews. Results: miR-21, miR-146a, miR-155, and miR-124, together with additional candidates such as miR-16, miR-92a, miR-93, miR-191, miR-499, miR-206 and miR-549a-3p, recurrently appeared across studies as associated with injury severity and neurological outcome measured by GCS, Glasgow Outcome Scale (GOS), or its Extended version (GOSE). Multi-miRNA panels generally outperformed individual miRNAs, and models integrating miRNAs with clinical variables reported higher discriminative performance than conventional single protein biomarkers alone. Across studies, the early post-injury window of approximately 24 to 72 hours appeared most informative for prognostication. Major barriers to translation include pre-analytical variability, the absence of consensus normalization strategies, and heterogeneity in analytical platforms and reporting. Conclusions: Circulating miRNAs represent a mechanistically grounded and logistically feasible candidate biomarker class for non-invasive TBI prognostication. Clinical translation will require multicenter validation, consensus pre-analytical and analytical standards, and phased implementation pathways adapted to local infrastructure. In Indonesia, leveraging the molecular diagnostic capacity expanded during the COVID-19 response could accelerate feasibility testing and early-phase clinical validation.